Analisis Sektor Ekonomi Unggulan Kabupaten Bangkalan - Astuti, Sisca Triyuni; Hidayat, Wahyu (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
This research was conducted to determine the basic and non-basic sectors, the classification of economic growth and the competitiveness of the economic sectors in Bangkalan Regency. In this study using a quantitative approach with Location Quotient analysis, Dynamic Location, Shift Share and Klassen Typology. The results obtained from the basic sector research are agriculture, forestry and fisheries, construction, government administration, defense, compulsory social security and education services. Meanwhile, the non-basic sector is the processing industry sector, electricity and gas procurement, water supply, waste processing, recycling waste, wholesale retail trade, motorbike car repair, transportation, warehousing, accommodation providers, food and drink, information, communication, financial services, insurance, corporate services, health services and social activities, and other services. So the government of Bangkalan Regency is expected to be able to develop the non-basic sector efficiently, so that the sector is able to support economic growth and increase the value of GRDP of Bangkalan Regency.